Sustainable Resource Management through Indigenous Knowledge and Practices – A Case of Food Security among the Baiga Tribe in India - Lakra, SJ, Sebestianus (European Journal of Sustainable Development, 2019)
India nurtures a tradition of rich civilization traceable from the antiquarian history and its primordial Indian village system. The linguistic relics, artifacts, rudiment tools and implements, skills of reading of the signs and seasons, mythic beliefs, tribal wisdom (sayings and proverbs), concepts and practices are foolproof of the existence of indigenous knowledge and practices. About 75% of global population is home to indigenous peoples and culture capable of deriving sustainable resource management. The knowledge of the local people tested over long period, adapted to local environment, then being passed down from one generation to another still has the carrying capacity of sustainable food security, health care, and ecological protection. The Baiga known for his cultural heritage, whose indigenous knowledge and practices is in transition but has relevance for sustainable resource management in resource depletion. The present work is an ethnographic study on the subject, in which the researcher used participant observation for data collection on food security through indigenous methods of farming. Open ended ethnographic interviews were conducted to the key informants. Keywords: Indigenous knowledge and practices, sustainable resource management, food security, Ethnographic, participant observation, organic farming, food security, Nutri cereals, Baiga Chak, PVTGs, D?hi